2018
DOI: 10.1080/13691457.2018.1461069
|View full text |Cite
|
Sign up to set email alerts
|

A personalised approach in activation. Workfare volunteers’ experiences with activation practitioners

Abstract: In activation worksupporting jobless people to perform activities that are supposed to lead them back to paid worka personalised approach is deemed crucial. What a personalised approach entails, however, remains unclear. In this article, we try to further develop the notion of a personalised approach in activation work, by analysing Dutch workfare volunteers' experiences with activation. Our interviews show that a personalised approach appears as a process with three stages. In the first stage, personalised me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
(31 reference statements)
1
5
0
Order By: Relevance
“…Research into the lived experience of workfare volunteerism has reported improved subjective well-being and 'soft gains', that is, relational and affective dimensions, as the most relevant for participants. Studies have reported lessening the effects of unemployment on well-being and employability by providing participants with opportunities for social interaction, access to self-respect, feeling appreciated, and displaying skills (Kampen et al, 2013;Slootjes and Kampen, 2017;De Waele and Hustinx, 2019;Kampen and Tonkens, 2019;Penny and Finnegan, 2019;Kampen, 2020). Nevertheless, research has shown that participants feel misrecognised for doing unpaid work while their regained self-respect can be short-lived and threatened by the limits of their obligatory tasks (Kampen et al, 2013).…”
Section: Contextmentioning
confidence: 99%
“…Research into the lived experience of workfare volunteerism has reported improved subjective well-being and 'soft gains', that is, relational and affective dimensions, as the most relevant for participants. Studies have reported lessening the effects of unemployment on well-being and employability by providing participants with opportunities for social interaction, access to self-respect, feeling appreciated, and displaying skills (Kampen et al, 2013;Slootjes and Kampen, 2017;De Waele and Hustinx, 2019;Kampen and Tonkens, 2019;Penny and Finnegan, 2019;Kampen, 2020). Nevertheless, research has shown that participants feel misrecognised for doing unpaid work while their regained self-respect can be short-lived and threatened by the limits of their obligatory tasks (Kampen et al, 2013).…”
Section: Contextmentioning
confidence: 99%
“…Third-party volunteering can apply mandatory pressures to have their constituency serve as volunteers. For instance, de Waele and Hustinx (2019) find that the "voluntary" property of volunteering is strongly violated in workfare volunteering as non-participation means losing welfare benefits (Kampen & Tonkens, 2019a). When service-learning is part of the curriculum, students are forced into volunteering to earn their study credits (Dienhart et al, 2016); when corporations engage in corporate volunteering, corporations must make a conscious choice between voluntary participation or mandatory pressures.…”
Section: Increasing Mandatory Pressures: Diminishing the Free Choice ...mentioning
confidence: 99%
“…Corporate volunteering, for instance, is often done during paid hours (Haski-Leventhal et al, 2010). In addition, the volunteers in workfare volun-teering are -indirectly -paid as the volunteer work enables the welfare recipients to keep their welfare benefits (Kampen & Tonkens, 2019a). Likewise, in service-learning, students receive study credits for their volunteer work.…”
Section: Stretching Volunteering To "Paid" Labourmentioning
confidence: 99%
See 2 more Smart Citations